ChemInform Abstract: Review: Mixed‐Valent Metallodendrimers: Design and Functions. Issue 3 (January 2015) - Astruc, Didier; Rapakousiou, Amalia; Wang, Yanlan; Djeda, Rodrigue; Diallo, Abdou; Ruiz, Jaime; Ornelas, Catia
Abstract Review: 56 refs.